A Comparison of Chronic Periodontitis in HIV-Seropositive Subjects and the General Population in the Ga-Rankuwa Area, South Africa - Razia Khammissa; Liviu Feller; Mario Altini; Paul Fatti; Johan Lemmer (AIDS Research and Treatment)
The effect of HIV infection on the prevalence and the rate of progression of chronic periodontitis is not clear. The aim of this study was to compare parameters associated with the severity of chronic periodontitis in terms of periodontal probing depths, gingival recession, plaque indexes, and bleeding indexes of HIV-seropositive subjects and healthy age-matched control subjects, and of HIV-seropositive subjects on highly active antiretroviral therapy and those not receiving such treatment. Two cohorts of subjects with chronic periodontitis were recruited for this study over a period of six months. There were 30 HIV-seropositive subjects, and 30 control subjects. Periodontal probing depths, gingival marginal recession, plaque indexes, and bleeding indexes were compared by HIV serostatus, the use of highly active antiretroviral therapy, and CD4+ T-cell counts. All participants were black persons between the age of 18 and 45 and were of a similar socioeconomic status and age. The results of this study indicate that chronic periodontitis in HIV-seropositive subjects is similar in terms of mean periodontal probing depth, gingival marginal recession, plaque index, and bleeding index to that in healthy age-matched control subjects, and a low CD4+ T-cell count does not appear to be a risk factor for increased severity of chronic periodontitis.